2009
DOI: 10.1107/s1600536809038641
|View full text |Cite
|
Sign up to set email alerts
|

Bis[aqua(2,3-naphtho-15-crown-5)sodium] tetrakis(thiocyanato-κN)cobaltate(II)

Abstract: The title complex, [Na(C18H22O5)(H2O)]2[Co(NCS)4], consists of two aqua­(2,3-naphtho-15-crown-5)sodium complex cations and one [Co(NCS)4]2− complex anion, which has crystallographic symmetry. In the anion, the CoII centre is coordinated by the N atoms of four NCS− ligands in a distorted tetra­hedral geometry. In the complex cations, the NaI centre is coordinated by five O atoms of the 2,3-naphtho-15-crown-5 ligand and one water O atom. The complex mol­ecules form a two-dimensional network via weak O—H⋯S inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…We expected that sodium would rather fit the ligand cavity as it usually does with crown ethers of this type and size, but we underestimated the influence of the counterion. Earlier infrared spectroscopic studies revealed that benzo-15-crown-5 ether forms a similar 2:1 sandwich with Na + , if the anion is tetraphenyl borate .…”
Section: Resultsmentioning
confidence: 95%
“…We expected that sodium would rather fit the ligand cavity as it usually does with crown ethers of this type and size, but we underestimated the influence of the counterion. Earlier infrared spectroscopic studies revealed that benzo-15-crown-5 ether forms a similar 2:1 sandwich with Na + , if the anion is tetraphenyl borate .…”
Section: Resultsmentioning
confidence: 95%